Depresssion, anxiety and other cognitive consequences of social isolation: Drug and non‐drug treatments. Issue 12 (14th October 2021) - Taheri Zadeh, Zahra; Rahmani, Shayan; Alidadi, Fatemeh; Joushi, Sara; Esmaeilpour, Khadijeh
Abstract: Objective: During the COVID‐19 pandemic, quarantine and staying at home is advised. The social relationship between people has become deficient, and human social isolation (SI) has become the consequence of this situation. It was shown that SI has made changes in hippocampal neuroplasticity, which will lead to poor cognitive function and behavioural abnormalities. There is a connection between SI, learning, and memory impairments. In addition, anxiety‐like behaviour and increased aggressive mood in long‐term isolation have been revealed during the COVID‐19 outbreak. Methods: Term searches was done in Google Scholar, Scopus, ScienceDirect, Web of Science and PubMed databases as well as hand searching in key resource journals from 1979 to 2020. Results: Studies have shown that some drug administrations may positively affect or even prevent social isolation consequences in animal models. These drug treatments have included opioid drugs, anti‐depressants, Antioxidants, and herbal medications. In addition to drug interventions, there are non‐drug treatments that include an enriched environment, regular exercise, and music. Conclusion: This manuscript aims to review improved cognitive impairments induced by SI during COVID‐19.